2022
DOI: 10.1055/s-0041-1740182
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the von Willebrand Factor—ADAMTS13 Axis, Complement Activation, and COVID-19 Severity and Mortality

Abstract: Background Endothelial and complement activation were both associated with immunothrombosis, a key determinant of COVID-19 severity, but their interrelation has not yet been investigated. Objectives We aimed to determine von Willebrand factor (VWF) antigen (VWF:Ag) concentration, VWF collagen binding activity (VWF:CBA), a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13 (ADAMTS13) activity (ADAMTS13:Ac), and their ratios in hospitalized COVID-19 patients, and to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 61 publications
(122 reference statements)
0
19
0
Order By: Relevance
“…The final full-text review included 163 reports, from which 123 studies did not meet the inclusion criteria and were excluded. A total of 40 studies comprising of 3764 patients met the including criteria and were included in this systematic review and meta-analysis [24] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] . Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The final full-text review included 163 reports, from which 123 studies did not meet the inclusion criteria and were excluded. A total of 40 studies comprising of 3764 patients met the including criteria and were included in this systematic review and meta-analysis [24] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] . Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The exact dynamic changes of VWF multimeric pattern after COVID-19 still need further study. The majority of studies reported normal or mildly to moderately decreased ADAMTS13:Ac levels [51] , [62] , [70] , [72] , [80] , [87] , and a strongly elevated VWF:Ag/ADAMTS13:Ac ratio in patients with COVID-19 when compared to healthy controls, especially in those with worse illness or in non-survivors [55] , [70] , [80] . We confirmed that lower levels of ADAMTS13:Ac and higher VWF:Ag/ADAMTS13:Ac ratio and VWF:Rco were related to poor clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The overactivation of the complement system releases C3 and C5 proteins, thus maintaining the inflammation and enhancing a hypercoagulable state. The point of convergence between the complement system and the coagulation cascade may lie in the presence of circulating ultra-large VWF molecules stemming from the reduced activity of the metalloproteinase ADAMTS13 caused by the SARS-CoV-2 infection 20 . It is hypothesized that these ultra-large VWF molecules may provide an additional surface for platelet adhesion and complement activation.…”
Section: Pathophysiologic Mechanisms Of Covid-19-associated Hypercoag...mentioning
confidence: 99%